A Novel Crimping Technique Approach for High Power White Good Plugs - Kivanc, Omer Cihan; Ozgonenel, Okan; Bostan, Omer; Guzel, Sahin; Demirsoy, Mert (TÜBİTAK Scientific & Technological Research Council of Turkey, 2022)
The crimping process is essential to human health and the durability of devices, especially in domestic appliances. Moreover, terminal crimping is critical to the safe transmission of electricity; incorrect crimping leads to problems including overheating of the plug, power loss, arc, and failure of the mechanical connection. In recent years, analysis has been performed by the finite element method (FEM) to prevent the incorrect design of crimping and to develop higher performance crimping techniques. A novel crimping technique for domestic appliances requiring high-powered plugs is proposed in this study. After defining the crimp parameters and the materials that are used for the crimp design, optimization is undertaken by using an analytical solver that uses both numerical calculation and finite element method analysis by COMSOL (TM) and Hyperworks. Prototypes are manufactured based on the result of the research, and capability analysis is performed using a histogram diagram. The feasibility and effectiveness of the proposed crimping technique for high-powered applications are validated by simulation and experimental studies.
Keywords: Finite Element Analysis; Crimping; Histogram Diagram; Manufacturing Technique; Capability Analysis